Diseño, construcción y evaluación de un hidrociclón para la remoción de arenas residuales en el desarenador en la planta de tratamiento de aguas residuales “La Totora”- Ayacucho. - Huallpa Vargas, Herlis Sergio (2024)
The research is part of the study of “Construction and evaluation of a hydrocyclone for the removal of residual sand in the sand trap at the “La Totora” WWTP, to determine the operating parameters of the hydrocyclone and the degree of removal of sand from the desander unit. The evaluated parameters of the sand trap channel operation were the following: Channel length: 30 m, channel width: 1.20 m, channel height: 2.50 m, channel working height 1.15 m, flow rate maximum: 0.650 m3/s, sand input concentration 0.12166 kg/m3 and sand output concentration 0.07746 kg/m3. The characterization of the residual sand accumulated in the sand trap unit was analyzed giving the following results: Organic matter content 10.7% that is impregnated into the sand, specific gravity 2.6208, apparent density 11,836 kg/m3, humidity 82.87%.